2023
DOI: 10.3390/toxins15030168
|View full text |Cite
|
Sign up to set email alerts
|

Compliance between Food and Feed Safety: Eight-Year Survey (2013–2021) of Aflatoxin M1 in Raw Milk and Aflatoxin B1 in Feed in Northern Italy

Abstract: Aflatoxins (AFs) are fungal metabolites that are found in feed and food. When ruminants eat feed contaminated with aflatoxin B1 (AFB1), it is metabolised and aflatoxin M1 (AFM1) is excreted in the milk. Aflatoxins can result in hepatotoxic, carcinogenic, and immunosuppressive effects. The European Union thus set a low threshold limit (50 ng/L) for presence of AFM1 in milk. This was in view of its possible presence also in dairy products and that quantification of these toxins is mandatory for milk suppliers. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The same research group [ 71 ] reported a parallel pattern of AFB1 contamination between some feeding stuff (>20 μg/kg), namely maize and cotton, and its metabolite AFM1 in raw milk (>50 ng/L) from dairy farms. These raw feed ingredients, which usually present the highest prevalence and values of AFB1, are candidates to serve as markers of contamination for this mycotoxin.…”
Section: Concepts Of Mycotoxins and Current Context In Dairy Cattlementioning
confidence: 99%
See 2 more Smart Citations
“…The same research group [ 71 ] reported a parallel pattern of AFB1 contamination between some feeding stuff (>20 μg/kg), namely maize and cotton, and its metabolite AFM1 in raw milk (>50 ng/L) from dairy farms. These raw feed ingredients, which usually present the highest prevalence and values of AFB1, are candidates to serve as markers of contamination for this mycotoxin.…”
Section: Concepts Of Mycotoxins and Current Context In Dairy Cattlementioning
confidence: 99%
“…The findings of both studies [ 69 , 71 ] emphasized the importance of regular surveillance plants considering different percentages and levels of mycotoxin contamination of raw feed as well as TMR in dairy farms. This realist approach can contribute to ensuring feed and food safety by monitoring both purchased and farm-produced feed.…”
Section: Concepts Of Mycotoxins and Current Context In Dairy Cattlementioning
confidence: 99%
See 1 more Smart Citation
“…When ruminants consume feed contaminated with AFB1, their bodies metabolize it, leading to the secretion of aflatoxin M1 (AFM1) in their milk. Aflatoxins are known to cause liver toxicity, cancerous effects, and suppression of the immune system (Ferrari et al, 2023). As noted by the World Health Organization (2018) also, AFM1 is associated with liver and kidney cancers and may potentially compromise the immune system, weakening its disease-fighting capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Peanuts, with rich nutrients and health value, are a type of important oil crop [ 5 ], but they are susceptible to aflatoxin contamination. Aflatoxins, with high toxicity, teratogenicity, and carcinogenicity, have been regarded as the most toxic mycotoxins found in food and agri-food [ 6 , 7 , 8 ], which not only threaten human health, but also can lead to huge economic losses [ 9 , 10 , 11 , 12 , 13 ]. Aflatoxins are secondary metabolites, mainly produced by Aspergillus flavus (A. flavus) in food and agri-food, especially peanuts and corn [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%